The Influence of Attachment Style on The Tendency of People Pleasing Behavior Among University Students in Kupang City - Melisa Soligracia Tanghana; Mernon Yerlinda Carlista Mage; Feronika Ratu (PSIKODIMENSIA Kajian Ilmiah Psikologi, 2025)
University students as early adults face developmental tasks in forming healthy interpersonal relathionship. People pleasing behavior tendency emerges as a respons to the need for acceptance and recognition in social environments. This study aims to determine the influence of attachment style on people pleasing behavior tendency among university students in Kupang City. The research method employed a quantitave approach with simple linear regression analysis using SPSS. The research sample was 382 respondents selected using a simple random sampling technique. Research instruments used the Inventory of Parent and Peer Attachment (IPPA) and The Disease to Please Triangle. The result of the analysis effect between attachment style and the tendency to engage in people pleasing behavior (β=-0,103; p0,05). This finding indicates that students with higher attachment style quality (tending to be secure) have a lower tendency to engage in people pleasing behavior.